Horses and ponies - Milbourne, Anna.; Gaudenzi, G. (Giacinto); Haggerty, Tim. (London : Usborne ; [Tulsa, Okla. : EDC], 2007)
Pictures and text provide an introduction to horses and ponies.
"Level 1"--Cover.
First published: London : Usborne, 2004.
Includes index.
IG 630
Accelerated Reader AR
Keywords: Horses -- Juvenile literature; Ponies -- Juvenile literature; Horses; Ponies